Linear Singularly Perturbed Systems - Starun, I. I.; ShkiI, N. I. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We investigate the solvability of the Cauchy problem for a linear singularly perturbed homogeneous system in the case of a singular pencil of matrices.